Strategi Pengembangan Usaha Melalui Event Marketing Lasagna Yukusiba di Jawa Barat - Kunanti Nurul Arifin; Sri Suwarsi; Mochamad Malik Akbar Rohandi (UNISBA Press, 2024)
Abstract. Pasta is recognized by UNESCO as an intangible cultural heritage of living things(intangible). Pasta is considered a traditional food that can develop over the years with a targetbrandt in Italy and around the world. Indonesia is a country with a high level of popularity with the Lasagna menu. Yukusiba is a business that offers lasagna products with a reach in West Java. The business development of Yukusiba is throughthroughevent marketing. This activity carries great potential to increase brand awareness, create a positive customer experience, and increase sales to Yukusiba. This study aims to determine the strategy that will be used by Yukusiba in business development throughevent marketing. This study focuses on identifying the potential for improvement and development in order to improve Yukusiba's performance. This research uses descriptive qualitative research methods and usescase study SWOT analysis, Porter’s Five Forces, Balance Scorecard, Target and Perfomance, dan Boston Consulting Group (BCG). Business development strategy This research will discuss several key aspects of business development strategy throughevent marketing for Yukusiba. The benefits of implementing the strategyevent marketing opportunities to gain media coverage will also be discussed. In conclusion, business development strategy throughevent marketing has great potential to advance Yukusiba. With careful planning, creative implementation, and effective collaboration, Yukusiba can take advantageevent marketing as a tool to expand market share, build customer connections, and take steps towards sustainable growth. Keywords: Event marketing, Business development, Pasta Abstrak. Pasta diakui oleh UNESCO sebagai warisan budaya tak berwujud mahluk hidup (intangible). Pasta dianggap sebagai makanan tradisional yang mampu berkembang di selama bertahun-tahun dengan target market di Italia dan seluruh dunia. Indonesia merupakan negara dengan tingkat popularitas tinggi dengan menu Lasagna. Yukusiba merupakan salah bisnis yang menawarkan produk lasagna dengan jangkuan di Jawa Barat. Pengembangan usaha dariYukusiba tersebut melalui melalui event marketing. Kegiatan tersebut ini membawa potensi besar untuk meningkatkan kesadaran merek, menciptakan pengalaman positif pelanggan, dan meningkatkan penjualan terhadap Yukusiba. Penelitian ini bertujuan untuk mengetahui strategi yang akan digunakan oleh Yukusiba dalam pengembangan usaha melalui event marketing. Penelitian ini berfokus pada identifikasi potensi perbaikan dan pengembangan guna meningkatkan kinerja Yukusiba Penelitian ini menggunakan metode penelitian deskriptif kualitatif dan menggunakan case study analisis SWOT, Porter’s Five Forces, Balance Scorecard, Target and Perfomance, dan Boston Consulting Group (BCG). Strategi pengembangan usaha Penelitian ini akan membahas beberapa aspek kunci strategi pengembangan usaha melalui event marketing bagi Yukusiba. Manfaat dari pelaksanaan strategi event marketing juga akan dibahas peluang untuk meraih liputan media. Dalam kesimpulan, strategi pengembangan usaha melalui event marketing memiliki potensi besar untuk memajukan Yukusiba. Dengan perencanaan yang matang, implementasi yang kreatif, dan kerja sama yang efektif, Yukusiba dapat memanfaatkan event marketing sebagai alat untuk memperluas pangsa pasar, membangun koneksi dengan pelanggan, dan mengambil langkah menuju pertumbuhan yang berkelanjutan. Kata Kunci: Event marketing, Pasta, Pengembangan usaha